Research on Homogenization Treatment of Mg-8wt.% Sn-1.5 wt.% Al Alloy. Issue 1 (May 2021) - Zhaoqian, Sun; Yongjun, Li; Kui, Zhang; Xinggang, Li; Minglong, Ma; Guoliang, Shi; Jiawei, Yuan
Abstract: The microstructure and morphology of Mg-8wt.%Sn-1.5wt.%Al alloy during homogenization were investigated by optical microscope (OM), scanning electron microscope (SEM), energy dispersive analysis (EDS) and HCT-3 comprehensive thermal analyzer. The results show that plenty of dendrite segregation arise in the as-cast alloy, and non-equilibrium eutectic phases distribute along the grain boundaries; at the same time, a large number of Sn and Al atoms segregated. The differential scanning calorimetry (DSC) curve shows that only one endothermic peak (549 °C) exists, which is caused by the redissolution of Mg2 Sn phase; according to the homogenization empirical formula, 460 °C to 500 °C is the appropriate heat period. However, surface oxidation appears when treated at 500 °C; so atmosphere (Ar2) protect was used, after treating for 500 °C×48 h, ideal resolution effect has been achieved.